Towards holictic concept of leadership in Islam for sustainable development community - Abdullah, Amini Amir; Esa, Masitah (Institut Sosial Malaysia, 2015)
Leadership has been connected with power, strategic planning, administration and management, controls, communication, influence, monitoring and evaluation. Identifying an effective leader is not an easy job. With regards to Islam, the concept of leadership is discussed extensively vis a vis within the purpose of the creation of man and his role as the vicegerent of Allah. The basis of Islamic political philosophy is the belief in the unity (tawhid) and sovereignty of Allah. It is only Allah who has the right to absolute loyalty. Loyalty to a leader, chief, nation or a monarch must be subordinated to this dominant factor. It is possible to be loyal to a leader and to Allah at the same time provided that loyalty to the former does not cause the abandon of Islamic teachings. Sustainable development needs a good leadership in order to achieve its goals effectively. Yet, there are other requirements; any decision must be made through agreement as a result of muzakarah (two way discussion) among committees in the organisation [Surah al-Shura (42): 38]. Consensus of opinion, understanding and unity of opinion (wahdat al-fikr) must be constructed in problem solving and issues. The decision which would be made should be based on what shura comes out with.